(untitled) (Research, Society and Development, 2021)
Background: for many decades apexification was the recommended treatment for immature permanent teeth with non-vital pulps. Currently, the revitalization of these teeth has been sought through pulp revascularization. This technique allows immature permanent teeth with non-vital pulps to complete root development, and uses biomaterials for this purpose. MTA is a calcium silicate cement, and is currently the most suitable biomaterial for cervical sealing in the pulp revascularization technique, but it has disadvantages. New biomaterials are being developed to try to improve some properties of the MTA. Objective: the aim of this study was to conduct a literature review comparing the physical, chemical and biological properties of MTA with the new biomaterials that are emerging on the market, for use in pulp revascularization. Conclusion: in the literature, the use of biomaterials such as Endosequence and Biodentine was found in pulp revascularization of immature permanent teeth with non-vital pulp, however, to date, there are no randomized clinical studies that prove the advantages of these materials in relation to MTA.